(untitled) (River Edge, NJ., 2004)
This book constitutes the proceedings of the 13th Course of the International School of Cosmic Ray Astrophysics. It focuses on major areas of astrophysics, their relation to cosmic ray physics, and our current understanding of the energetic processes in the Galaxy and the Universe that govern the acceleration and form the features of the cosmic rays that we detect at Earth.
Keywords: Astrophysics,Cosmic rays,Cosmology; Vật lý học thiên thể,Vũ trụ học